Identification of oligo-adenylated small RNAs in the parasite Entamoeba and a potential role for small RNA control - Zhang, Hanbang (BMC Genomics, 2020)
BACKGROUND: The RNA interference (RNAi) pathway is a gene regulation mechanism that utilizes small RNA (sRNA) and Argonaute (Ago) proteins to silence target genes. Our previous work identified a functional RNAi pathway in the protozoan parasite Entamoeba histolytica, including abundant 27 nt antisense sRNA populations which associate with EhAgo2–2 protein. However, there is lack of understanding about the sRNAs that are bound to two other EhAgos (EhAgo2–1 and 2–3), and the mechanism of sRNA regulation itself is unclear in this parasite. Therefore, identification of the entire pool of sRNA species and their sub-populations that associate with each individual EhAgo protein would be a major step forward. RESULTS: In the present study, we sequenced sRNA libraries from both total RNAs and EhAgo bound RNAs. We identified a new population of 31 nt sRNAs that results from the addition of a non-templated 3–4 adenosine nucleotides at the 3′-end of the 27 nt sRNAs, indicating a non-templated RNA-tailing event in the parasite. The relative abundance of these two sRNA populations is linked to the efficacy of gene silencing for the target gene when parasites are transfected with an RNAi-trigger construct, indicating that non-templated sRNA-tailing likely play a role in sRNA regulation in this parasite. We found that both sRNA populations (27 nt and 31 nt) are present in the related parasite Entamoeba invadens, and are unchanged during the development. In sequencing the sRNAs associating with the three EhAgo proteins, we observed that despite distinct cellular localization, all three EhAgo sRNA libraries contain 27 nt sRNAs with 5′-polyphosphate (5′-polyP) structure and share a largely overlapping sRNA repertoire. In addition, our data showed that a fraction of 31 nt sRNAs associate with EhAgo2–2 but not with its mutant protein (C-terminal deletion), nor other two EhAgos, indicating a specific EhAgo site may be required for sRNA modification process in the parasite. CONCLUSION: We identified a new population of sRNA with non-templated oligo-adenylation modification, which is the first such observation amongst single celled protozoan parasites. Our sRNA sequencing libraries provide the first comprehensive sRNA dataset for all three Entamoeba Ago proteins, which can serve as a useful database for the amoeba community. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-020-07275-6.